Adaptation of gutta percha to oval canals: A cone beam computed tomographic analysis - De Vasconcelos, Rafaela Andrade [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Das Neves Cavalcanti, Bruno; Manhães, Luiz Roberto Coutinho; Gonçalves, Simone Helena Ferreira (My University, 2017)
This study evaluated the influence of different instrumentation techniques on the adaptation of gutta percha cones in oval-shaped root canals. A total of 90 human single-rooted teeth were divided into groups according to the instrumentation technique that was used: group M, manual; group OM, hybrid: oscillatory plus manual; group PT, rotary (ProTaper Universal); group OPT, hybrid: oscillatory plus rotary (ProTaper Universal); group MT, rotary (Mtwo); and group OMT, hybrid: oscillatory plus rotary (Mtwo). After a single gutta percha cone was adapted to the canal, cone beam computed tomography was utilized to perform assessments at areas of greater contact of gutta percha to root canal walls. The adaptation was rated as ideal, satisfactory, minimally acceptable, or unsatisfactory. The frequency of ideal adaptation of the cone to the 4 canal walls varied from 26.67% (groups OMT and PT) to 73.33% (group MT); the differences between group MT and groups PT and OMT were statistically significant (P < 0.05). The mean area of the canal preparation without adaptation (contact) of the cone varied from 0.06 mm2 (group MT) to 0.41 mm2 (group OMT). The results showed that an instrumentation technique using the Mtwo system provided the best adaptation of the .04 gutta percha cones to anatomically oval root canals.
Keywords: Computed tomography; Instrumentation; Obturation; Single cone